Apical Transportation and Centering Ability After Root Canal Filling Removal Using Reciprocating and Continuous Rotary Systems: A CBCT Study - Arruda, Etienny da Silva; Sponchiado-Júnior, Emílio Carlos; Pandolfo, Mariana Travi; Fredson, Márcio Acris de Carvalho; Roberi Garcia, Lucas da Fonseca; Marques, André Augusto Franco (European Journal of Dentistry, 2019)
Objective To evaluate the apical transportation and centering ability promoted by reciprocating and continuous rotary systems after root canal filling removal.Materials and Methods After obturation, 40 mesial root canals of mandibular molars were distributed into four groups (n = 20) for filling material removal: PTU group–F2 instrument (25.08) of ProTaper Universal system; R25 group–R25 instrument (25.08) of Reciproc system; X2 group–X2 instrument (25.06) of ProTaper Next system and X3 group–X2 instrument (25.06) of ProTaper Next system, followed by X3 instrument (30.07). Cone-beam computed tomographic analysis was performed before and after filling material removal for acquisition of apical images. Apical transportation (AT) and its direction, and centering ability (CA), were assessed using the equations AT = (X1–X2)–(Y1–Y2) and CA = (X1–X2/Y1–Y2 or Y1–Y2/X1–X2), respectively. Data were submitted to the nonparametric Kruskal–Wallis and Dunn multiple comparison tests (p < 0.05) for statistical analysis.Results There was no statistically significant difference among groups for AT (p > 0.05), with a tendency toward transportation in the distal direction. Also, there was no statistically significant difference among groups regarding CA (p > 0.05).Conclusions The different systems, including ProTaper Next, caused AT within the acceptable clinical limit after filling removal. In addition, none of the tested systems presented adequate CA.
Keywords: Apical transportation; centering ability; rotary systems; reciprocating motion